2022
DOI: 10.5829/ije.2022.35.12c.06
|View full text |Cite
|
Sign up to set email alerts
|

Stern Flap Application on Planing Hulls to Improve Resistance

Abstract: Drag is one of the main factors in improving fuel efficiency. Various study in regards to improve drag performance of a planing hull amongst them is a stern flap. The main parameters to design a stern flap are span length and angle of stern flap. The stern flap works by changing pressure distribution over the ship's bottom and creating a lift force on the stern transom part. This study aims to analyze the behavior of stern flap in variations of span length and angle of stern flap towards drag performance of Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…This trim control can be an interceptor, stern flap, or stern foil 102) . Many studies agree that trim control can reduce unwanted trim angles at high speeds, including the interceptor 79), [103][104][105] , stern flap [106][107][108] , and stern foil 109,110) . Fig.…”
Section: Trim-control Definition and Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…This trim control can be an interceptor, stern flap, or stern foil 102) . Many studies agree that trim control can reduce unwanted trim angles at high speeds, including the interceptor 79), [103][104][105] , stern flap [106][107][108] , and stern foil 109,110) . Fig.…”
Section: Trim-control Definition and Functionmentioning
confidence: 99%
“…Budiarto et al 106) performed a CFD simulation to analyze the application of the stern flap to the Fridsma's hull, with a variation of Fr 0.89-1.78. The analysis findings indicate a positive impact of the stern flap on reducing ship resistance, including pressure drag and friction drag.…”
Section: Trim Tabmentioning
confidence: 99%
“…The result shows that the global effect due to motions and local effects referenced to the stern flap and the waterjets are the leading causes of drag increase, with the non-linear coupling term of local effects contributing the most to drag reduction. Li et al [16] and Budiarto et al [17] studied the effect of stern flaps on a ship in regular waves and high-speed conditions, respectively, and Tripath and Vijayakumar's found that flaps affect trim, sinkage, and propulsion, while the wave suppression improves performance [18].…”
Section: Introductionmentioning
confidence: 99%
“…Deng et al [17] numerically examined interceptor impact on the viscous flow field of deep-V vessels, focusing on alterations in resistance, lift, and distributions of base pressure and stern velocity. Budiarto et al [18] numerically probed the effects of the SF on the resistance components of planing vessels and determined that ship and component resistance can be achieved by adjusting the pitch and heavy value of the ship to decrease its displacement.…”
Section: Introductionmentioning
confidence: 99%